1994
DOI: 10.1248/bpb.17.1012
|View full text |Cite
|
Sign up to set email alerts
|

Anti-ulcer Effects of Lactic Acid Bacteria and Their Cell Wall Polysaccharides.

Abstract: The anti-ulcer effects of bifidobacteria, lactobacilli and streptococci were examined using the acetic acid-induced gastric ulcer and ethanol-induced erosion models in rats. Bifidobacterium breve YIT4014 and 4043, and Bifidobacterium bifidum YIT4007 were administered orally, and anti-ulcer effects were confirmed for not only these organisms but also their polysaccharide fractions (PSFs). The major component of these anti-ulcer polysaccharides was rhamnose. In particular, polysaccharides in which the rhamnose c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
2
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 2 publications
1
62
2
1
Order By: Relevance
“…These results suggest that a metabolite(s) of these bacteria plays an important role in the prevention of ileal ulcer formation. Nagaoka et al (25) reported that lactic acid bacteria and their cell wall polysaccharides were effective for healing gastric ulcers induced by acetic acid. However, in our study, cells of L. acidophilus and B. adolescentis were not effective.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that a metabolite(s) of these bacteria plays an important role in the prevention of ileal ulcer formation. Nagaoka et al (25) reported that lactic acid bacteria and their cell wall polysaccharides were effective for healing gastric ulcers induced by acetic acid. However, in our study, cells of L. acidophilus and B. adolescentis were not effective.…”
Section: Discussionmentioning
confidence: 99%
“…9,10) EPSs have been shown to benefit human health by their immunomodulation, anti-gastritis, anti-ulcer, and anti-virus activities. [11][12][13] We have shown that P. pentosaceus LP28 has the strain-specific EPS biosynthetic gene cluster, 14) and intake of the strain is effective to improve the high fat diet-induced obesity and fatty liver of the mice. 6) Furthermore, the strain is also useful to reduce body fat and body weight in human clinical study.…”
mentioning
confidence: 99%
“…Uejima et al (18) founded that Lactobacillus inhibited non-steroidal anti-inflammatory druginduced ileal ulcer in rats by repressing the growth of ulcer-inducing bacteria, the Gram-negative facultative anaerobic rods Esherichia coli, Klebsiella, and Proteus, although the ulcer models were different than the models used in the present study or Elliott's model. On the other hand, Nagaoka et al (19) reported that polysaccharide of Lactobacillus cell wall had a gastroprotective effect and the content of rhamnose was important. Indeed, in this study, non-fermented milk did not inhibit the lesion formation.…”
mentioning
confidence: 99%